Nanodomains Coupled to Ferroelectric Domains Induced by Lattice Distortion in Self-Doped LuMnxO3 +/-delta Hexagonal Ceramics - Baghizadeh, A.
Self-doped h-LuMnxO3 +/-delta multiferroic ceramics with 0.92 <= x <= 1.12 were studied for the dependence of: magnetic properties on x. Interlocking of lattice distortion at the nanoscale with ferroelectric (FE) domains in bulk RMnO3 materials is, mostly unknown. Here we report occurrence of nanodomains in transmission electron microscopy (TEM) images with the presence of antiphase boundaries/ferroelectric domain walls separating nano-FE domains. Observed chemical inhoi-nogeneity across the crystalline grains of the ceramics causes distortion in the lattice. Formation of nanostructural domains revealed across particles of Mn deficient or Lu, deficient samples includes bands of Strained atomic planes, structural antiphase boundaries, and planar defects similar to stacking fault ribbons. Nanotwins exist in the basal plane, the twin boundary representing disorder of the stacking of atomic planes along the [110] direction. Image contrast in high resolution HRTEM images and TEM linage simulation confirm the role of planar defects,on switching of polarisation, which, cause topology breaking of sixfold vortices,of FE domains in h-RMnO3 oxides. The local orbital arrangements of ions are investigated by EELS spectroscopy of O K-edge supported by theoretical analysis: Irreversibility in magnetization below the Neel temperature of antiferromagnetic ordering of the h-LuMnxO3 +/-delta multiferroic solid solution is found for all ceramics showing dependence on cation vacancy type and nominal content. The main features Observed in the irreversibility of magnetization were correlated to defects and inhomogeneity in the nanoscale images of the lattice of ceramics. The interplay of lattice distortion linked to extended defects and magnetic/ferroelectric properties of multiferroic ceramics is further discussed.